Abundant a proliferation-inducing ligand (APRIL)-producing macrophages contribute to plasma cell accumulation in immunoglobulin G4-related disease. Issue 6 (15th October 2018) - Kawakami, Takahiro; Mizushima, Ichiro; Yamada, Kazunori; Fujii, Hiroshi; Ito, Kiyoaki; Yasuno, Tetsuhiko; Izui, Shozo; Yamagishi, Masakazu; Huard, Bertrand; Kawano, Mitsuhiro
Abstract: Background: This study aimed to investigate the contribution of a proliferation-inducing ligand (APRIL), a member of the tumor necrosis factor (TNF) superfamily implicated in plasma cell survival, to the development of plasma cell–rich lesions in immunoglobulin G4–related disease (IgG4-RD). Methods: We performed immunohistochemical staining for APRIL with Stalk-1 and Aprily-8 antibodies specifically recognizing APRIL-producing cells and secreted APRIL, respectively, in renal and submandibular lesions of IgG4-RD in comparison with those of Sjögren's syndrome and sialolithiasis. Results: Numerous Stalk-1-positive APRIL-producing cells were detectable in lesions of IgG4-RD. These cells, identified as CD163-positive M2 macrophages, secreted APRIL that distributed close to and even on infiltrating plasma cells. In contrast, APRIL-producing cells and the secreted form of APRIL were rarely detectable in lesions of Sjögren's syndrome or sialolithiasis. Notably, APRIL expression decreased concomitantly with the level of plasma cell infiltration after successful glucocorticoid treatment. Conclusions: Abundant infiltration into tissue lesions of APRIL-producing M2 macrophages and retention of secreted APRIL in plasma–cell–rich areas support a role for APRIL in the pathogenesis of plasma cell–rich lesions in IgG4-RD.